Evaluation of the impact of M&A on acquiring shareholder wealth and the key determinants in US and China market - CAO, ZHURU (2019)
This paper investigates the impact of merge and acquisition (M&A) on shareholder wealth measured by stock abnormal return of acquirers located in US and China in both short-term and long-term. The stock performance of US acquirers has been widely studied and relatively consistent opinion have been reached. In contrary, the evidence for M&A’s in China is mixed. Hence, this paper aims to examine the past evidence in US M&A market within the latest data, and update security reaction to M&A events in Chinese market as well. Total 312 numbers of deals, with 106 deals for each country, are sampled during 2013 to 2015. Event study methodology is applied to detect abnormal return around announcement and over post-announcement period. Moreover, the influence of potential determinants on shareholder wealth such as firm size, target size, relative countries of participants, market-to-book value, target type and industry relatedness would be investigated via sub-sample analysis, implemented by separating full sample into several sub-groups based upon corresponding factors. Finally, a multivariate analysis of OLS regression would be conducted to find out the relationship between stock return and key factors. Our results show that insignificant and significant positive abnormal return to acquirers are observed respectively around announcement in US and Chinese market, whereas bidding shareholders would suffer from significant and insignificant stock loss over 2-year post-announcement period in US and China. In addition, sub-samples analysis highlights that smaller-sized, higher ROE and leverage bidders with private target would significantly perform better in US, meanwhile, acquisitions with larger-sized bidders, related industry, private targets and different countries of participants would significantly destroy acquirers’ wealth in China. However, the influence of M&A on bidding shareholder wealth shows different patterns in two countries. The particularities of state-owned-entity and non-tradeable shares in China, as well as different developing degree of security market could contribute to the distinction of two countries’ M&A market.